Nanoscale structure and dynamics of ABOBEC3G complexes with single-stranded DNA - Shlyakhtenko, Luda S. (2012)
The DNA cytosine deaminase APOBEC3G (A3G) is capable of blocking retrovirus replication by editing viral cDNA and impairing reverse transcription. However, the biophysical details of this host-pathogen interaction are unclear. Here we applied atomic force microscopy (AFM) and hybrid DNA substrates to investigate properties of A3G bound to single-stranded DNA (ssDNA). Hybrid DNA substrates included ssDNA with 5′ or 3′ ends attached to DNA duplexes (tail-DNA) and gap-DNA substrates, in which ssDNA is flanked by two double-stranded fragments. We found that A3G binds with similar efficiency to the 5′ and 3′ substrates, suggesting that ssDNA polarity is not an important factor. Additionally, we observed that A3G binds the single-stranded region of the gap-DNA substrates with the same efficiency as tail-DNA. These results demonstrate that single-stranded DNA ends are not needed for A3G binding. The protein stoichiometry does not depend on the ssDNA substrate type, but the ssDNA length modulates the stoichiometry of A3G in the complex. We applied single molecule high-speed AFM to directly visualize the dynamics of A3G in the complexes. We were able to visualize A3G sliding and protein association-dissociation events. During sliding, A3G translocated over a 69 nucleotide ssDNA segment in less than 1 second. Association-dissociation events were more complex, as dimeric A3G could dissociate from the template as a whole, or undergo a two-step process with monomers capable of sequential dissociation. We conclude that A3G monomers, dimers, and higher order oligomers can bind ssDNA substrates independent of strand polarity and availability of free ssDNA ends.